Análise dos processos educativos para profissionais de enfermagem em um hospital filantrópico do Estado de São Paulo - Gomes, Daniele Perez (Universidade Federal de São Carlos, 2023)
The nursing team is the main force involved in hospital care, and its work processes have a major impact on the permanence and quality of care. Therefore, to achieve the objectives of health services, employees highlight working conditions, both structural and human resources, as well as investment in training and space for reflection on their practice, ensuring good performance. Given the evolution of educational actions for health professionals, according to the National Policy for Permanent Health Education (NPPHE), it is understood that Permanent Health Education (PHE) and Continuing Education (CE) complement each other as in-service training strategies, even if they are based on different methodological principles. Together, they allow professional improvement and reflection on work processes, enhancing the change in reality. Points were considered that involve the complexity of the work, the importance of the nursing team for care processes, the evolution of their bureaucratic activities, the need for investment in in-service training, the educational role to be strengthened by the nurse, stimulating reflection on practice, identifying challenges and proposing solutions, as well as the differentiation between CE and PHE. The present study is part of the line of research “Management of Care, Work and Education in Health” of the Postgraduate Program in Clinical Management at the Federal University of São Carlos (UFSCar), and as it is a Professional Master's Degree, it has close relationship with health policies; Thus, it was proposed to identify the perceptions of nursing professionals at a philanthropic hospital about the educational actions aimed at them and provide support for more appropriate educational strategies. A descriptive research with a qualitative approach was carried out, with the participation of 9 nursing professionals. The information was collected remotely, through semi-structured interviews, which were recorded and transcribed, allowing the Thematic Content Analysis, proposed by Bardin, to be carried out with the help of the Atlas.ti® software. The methodology identified concepts, facilitators and obstacles, qualification needs and suggestions for changes. The results showed that there is a lack of familiarity among professionals with PHE, highlighting confusion with CE. Work overload and the reduced number of employees were highlighted as the main difficulties in participating in educational activities during shifts. Professionals expressed the need for training to deal with everyday challenges, preferring practical training and despite the difficulties, PHE was recognized as a valuable tool for improving the work process and the quality of care. It is concluded that the main necessary change in educational practices is related to management, which should involve front-line employees in the decisions made, as well as the importance of educators knowing the reality of each sector and requesting the participation of employees in the preparation of educational actions. The results will be presented to the study institution through a technical report, which will serve as a reference for the development of educational strategies that are more appropriate to the reality of nursing professionals in hospital services.
Analysis of educational processes for nursing professionals in a philanthropic hospital in the state of São Paulo
Keywords: Educação permanente; Educação continuada em enfermagem; Capacitação de recursos humanos em saúde; Serviços hospitalares; Hospitais filantrópicos; Serviço hospitalar de educação; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO